2018
DOI: 10.18671/scifor.v46n120.09
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between compression strength parallel of wood and charcoal of Eucalyptus clones

Abstract: A complexidade do ensaio e a ausência de normas técnicas para os testes de compressão dificultam a determinação das propriedades mecânicas do carvão vegetal, que estão diretamente relacionadas à qualidade e utilização. O objetivo deste trabalho foi avaliar e correlacionar as propriedades mecânicas da madeira e do carvão vegetal de 11 clones de Eucalyptus sp. Discos de madeira com espessura de 5 cm foram retirados em diferentes posições da altura comercial do tronco. As carbonizações foram realizadas em forno e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Industries in the energy sector aim for a minimum percentage of 28% lignin content for wood (Pereira et al, 2013b). Protásio et al (2014), Santos et al (2011), andArantes et al (2011) found mean values of 32%, 29.75%, and 31.05%, respectively, for lignin content in Eucalyptus spp. clones.…”
Section: Charcoalmentioning
confidence: 89%
“…Industries in the energy sector aim for a minimum percentage of 28% lignin content for wood (Pereira et al, 2013b). Protásio et al (2014), Santos et al (2011), andArantes et al (2011) found mean values of 32%, 29.75%, and 31.05%, respectively, for lignin content in Eucalyptus spp. clones.…”
Section: Charcoalmentioning
confidence: 89%
“…When charcoal is buried in soil, it will be crushed via compression due to overlying strata. Therefore, we adopted a standard compression testing machine (Landmark 370.10) to perform compression experiments on charcoal samples to simulate the pressure exerted by overlying formations, the experiments were performed in the open laboratory of Chang’an University [ 37 , 40 ]. Compression was applied along the radial longitudinal direction (perpendicular to the fibers), and the descending speed was set to 2 mm/min for 30s from the time of contact with the sample, i.e., the descending displacement was 2.5 mm (the charcoal height was approximately 12–13 mm).…”
Section: Methodsmentioning
confidence: 99%